Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea - Sonnenberg, Rainer; Blum, Thomas; Misof, Bernhard Y. (Zootaxa, 2006)
Episemion krystallinoron sp. nov., the second species in this formerly monotypic genus, is described from the Monts de Cristal in northwestern Gabon and adjacent areas in Equatorial Guinea. It is clearly distinguished from its congener by the coloration pattern of adult males. Species status is also supported by mitochondrial DNA data. Episemion Radda & Pürzl, 1987 is regarded as a valid genus, distinct from all other nothobranchiid genera and probably most closely related to Diapteron Huber & Seegers, 1977 and Kathetys Huber, 1977. It is the third described endemic nothobranchiid species from the Monts de Cristal and adjacent areas.